Radio frequency circuit design based on variable resistance active inductor - Babaei Kia, Hojjat (2013)
Amongst design challenges in designing Complementary Metal-Oxide- Semiconductor (CMOS) active inductors are to produce high inductance and high tune-ability within an acceptable quality factor in a specific frequency range. The need for these design qualities is apparent in Radio Frequency (RF) circuits such as filters, Low Noise Amplifiers (LNAs) and Voltage-Controlled Oscillators (VCOs). This thesis focuses on the above issues to design tunable active inductor circuits and offers a design approach which partially solves some of the design challenges. Three active inductor circuits with comparable or better performance in terms of high inductance and tune-ability are produced from this research work. These active inductors which have been designed using Cadence Spectra based on CMOS 0.18 µm Silterra process have high tune-ability, high quality factor and wide tuning range. Their inductance tune-ability ranges from 5 nH to 500 nH with a frequency range of 1 GHz to 7 GHz and the quality factor range of 30 to 700. The power dissipation is from 1.9 mW to 6.5 mW from a 1.8 V DC power supply. The inductance can be tuned by tuning the variable resistance within the active inductor itself. The active inductors have been employed in LNA and VCO circuits where their output frequency range is changed by tuning the variable resistor. The simulation result for the LNA shows a frequency range of 1 GHz to 2.5 GHz with high gain (S21), low input return loss (S11), low output return loss (S22) and low noise figure. For the VCO, the oscillating frequency ranges from 0.5 GHz to 2.2 GHz with low chip size, high Kvco and high output power.